A 16-year Remained UroLume Stent without any Complication; a Case Report - Jalil Hoseini, Seyed; Moftakhari Hajimirzaei, Shideh; Sharifian Amiri, Rayka; Shojaeefar, Ehsan; Mirjalili, Ali Mohammad (Urology Journal, 2021)
Lumen diameter reduction which is called urethral stricture has several causative agents including iatrogenic, inflammatory, traumatic, and idiopathic factors. The main treatment options are transurethral or open surgical interventions.The UroLume which was introduced around 33 years ago is an intraurethral stent and as a temporary treatment approach has a maximum 9-month durability, but here we present the first ever reported forgotten 16-year remained UroLume without any complication.